Exploration of Semantic Frames to Confirm Verb Meaning - Pasaribu, Asril Rouli Nilawati; Simanjuntak, Tesa Arizky; Sari, Yuliana (CV. Rayyan Dwi Bharata, 2024)
Semantics is one of three levels of language analysis: phonological, grammatical, and semantic. Semantics is a field of linguistics that studies the relationship between linguistic signs and the objects they signify, or in other words, a field of linguistic study that investigates what language means and means. Semantics is a field of linguistics that is closely related to other social sciences, such as sociology or anthropology, and even to philosophy and psychology. Sociology is related to semantics due to the fact that the identity of social groups can be demonstrated by the use of certain words to indicate meaning.